2002
DOI: 10.1046/j.1365-2214.2002.00300.x
|View full text |Cite
|
Sign up to set email alerts
|

Oscillating between hope and despair — a qualitative study

Abstract: Chronic pain is a substantial problem for children with JCA, which must be considered in health care. The pain affected and disturbed the children's ordinary way of life. It blocked a number of goals. Psychological and physiological processes interact in the phenomenological experience of pain, and the response of the environment elicits, maintains or decreases the experience of pain. Hopefully,the findings contribute to a deeper understanding of the life situation of children suffering from JCA and can be of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
80
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(86 citation statements)
references
References 20 publications
(26 reference statements)
4
80
0
2
Order By: Relevance
“…Ungerer and colleagues (1988) have pointed out the social consequences of arthritis for teenagers, compared with younger children. The results of our earlier studies clarify that those children's (6Á17 years) interpersonal relations are negatively affected by pain associated with chronic arthritis (Sällfors et al, 2001(Sällfors et al, , 2002. In addition to increasing developmental challenges, pain and illness create additional challenges related to coping for teenage girls with chronic arthritis.…”
Section: Discussionmentioning
confidence: 92%
“…Ungerer and colleagues (1988) have pointed out the social consequences of arthritis for teenagers, compared with younger children. The results of our earlier studies clarify that those children's (6Á17 years) interpersonal relations are negatively affected by pain associated with chronic arthritis (Sällfors et al, 2001(Sällfors et al, , 2002. In addition to increasing developmental challenges, pain and illness create additional challenges related to coping for teenage girls with chronic arthritis.…”
Section: Discussionmentioning
confidence: 92%
“…The results indicate that there is variation in pain and, therefore, the children could live like their healthy peers one day, only to realize another day that "the pain had taken over." They expressed a sense of frustration, powerlessness, and uncertainty about the future (26 …”
Section: Invisible Painmentioning
confidence: 99%
“…. because I didn't have a bandage or anything" (26). "People don't understand that one day you can be okay and the other day, that you can't.…”
Section: Invisible Painmentioning
confidence: 99%
See 1 more Smart Citation
“…Sallfors, Fasth and Hallberg (2002) spoke to children living with juvenile chronic arthritis and found that children did not perceive that health professionals and school staff trusted their reporting of their illness experience. The children expressed readiness to participate in the relationship and felt able to ask questions however they did not often feel supported in doing so.…”
Section: A Child's Viewmentioning
confidence: 99%